Catheter ablation for atrial arrhythmias in adults with congenital heart disease: recurrence rates and predictors of acute procedural success. (24th May 2021) - El-Medany, A; Sunderland, N; Dobson, R; Nisbet, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Heart rhythm disorders are an important cause of morbidity and emergency hospitalisation in patients with adult congenital heart disease (ACHD), and this is due to a combination of surgical scar, residual haemodynamic lesions, and cardiac chamber dilatation. The most effective available treatment is catheter ablation, although this can be extremely challenging owing to abnormal anatomy and problems accessing intra cardiac sites critical to the arrhythmia mechanism. However, outcomes of catheter ablation and analysis of factors which may predict recurrence of arrhythmia remain poorly defined.  Purpose   To define the cohort of ACHD patients undergoing catheter ablation for atrial arrhythmia in a large tertiary centre, characterise outcomes, and determine factors associated with arrhythmia recurrence. Methods: Retrospective study of all catheter ablations for atrial arrhythmias in ACHD patients between April 13, 2016 and December 16, 2019 at our institution.  Patients were identified using a field search through a centralised database; and pre-specified clinical and procedural data of interest, and time from ablation to recurrence were determined from the computerised electronic record. Binary logistical regression and cox regression analysis were used to determine potential predictors of acute procedural success and arrhythmia recurrence respectively.  Results: Among 90 patients (mean age 43 ± 15 years) who underwent catheter ablation for atrial arrhythmia, 39 (43%) were treated for macro-reentrant atrial tachycardia, 19 (21%) for focal atrial tachycardia, 9 (10%) for multifocal atrial tachycardia, 10 (10%) for atrial fibrillation, 7 (8%) for atrioventricular nodal reentrant tachycardia, and 6 (7%) for atrioventricular reentrant tachycardia. 35 (39%) of patients had "severe" complexity ACHD as per the Bethesda classification. 35 (39%) experienced recurrent arrhythmia with a median time to recurrence of 120 days. Age, gender, body mass index, complexity of congenital heart disease, and previous surgical repair were not identified as being significantly associated with recurrence, however univariate cox regression analysis showed a significantly longer time to recurrence in cases utilising electroanatomical mapping and demonstrating non-inducibility of arrhythmia in the lab post ablation (p < 0.001). There was 1 case of post-ablation bradycardia requiring pacemaker implantation, but no other complications. Conclusion: Catheter ablation for atrial arrhythmia in ACHD patients is safe and effective, with a majority of patients achieving multiple arrhythmia-free months. Non-inducibility of arrhythmia post procedure and use of electroanatomical mapping are predictors of freedom from recurrence of atrial arrhythmia, suggesting effective characterisation and ablation of the arrhythmia mechanism is more important than the underlying substrate. These findings may aid management decisions for recurrent arrhythmia in ACHD patients.